KAJIAN TENTANG MASALAH INTELEKTUAL DALAM KAITANNYA DENGAN PRESTASI BELAJAR ANAK USIA SEKOLAH - Riska Yulianti; Nesa Nathania; Whidya Marsyha Angelyna; Romiaty Romiaty (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Intellectual problems in school-age children have become a significant concern in education due to their impact on academic achievement. This study aimed to analyze the influence of intellectual problems on the academic achievement of school-age children through a literature review method. Data were collected from various scientific sources, including journals, books, and theses published in the last ten years, then analyzed descriptively and qualitatively. The results show that intellectual problems have a significant and multidimensional influence on academic achievement, encompassing cognitive factors (intelligence and specific learning difficulties), health factors (stunting and nutritional deficiencies), psychological factors (mindset and motivation), and environmental factors (stimulation and social support). Intelligence serves as an important foundation but is not the sole determinant of academic achievement, as motivation, self-regulation, self-efficacy, and multiple intelligences also play significant roles. Stunting is negatively correlated with children's intellectual abilities through biological mechanisms involving impaired neuronal myelination. A growth mindset contributes positively to children's academic resilience. In conclusion, a holistic approach involving collaboration between the education and health sectors, early identification, and mindset-based interventions is essential to optimize the academic achievement of school-age children. ABSTRAK Masalah intelektual pada anak usia sekolah menjadi perhatian penting dalam dunia pendidikan karena berdampak pada prestasi belajar. Penelitian ini bertujuan untuk menganalisis pengaruh masalah intelektual terhadap prestasi belajar pada anak usia sekolah melalui metode studi pustaka. Data dikumpulkan dari berbagai sumber ilmiah berupa jurnal, buku, dan skripsi yang dipublikasikan dalam sepuluh tahun terakhir, kemudian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa masalah intelektual berpengaruh signifikan dan multidimensional terhadap prestasi belajar, mencakup faktor kognitif (intelegensi dan kesulitan belajar spesifik), faktor kesehatan (stunting dan defisiensi gizi), faktor psikologis (mindset dan motivasi), serta faktor lingkungan (stimulasi dan dukungan sosial). Intelegensi berperan sebagai fondasi penting tetapi bukan penentu tunggal prestasi belajar, karena motivasi, regulasi diri, efikasi diri, dan kecerdasan majemuk juga berperan signifikan. Stunting berkorelasi negatif dengan kecerdasan intelektual anak melalui mekanisme biologis gangguan mielinisasi sel saraf. Growth mindset berkontribusi positif terhadap ketahanan akademik anak. Simpulannya, pendekatan holistik yang melibatkan kolaborasi sektor pendidikan dan kesehatan, identifikasi dini, serta intervensi berbasis mindset sangat diperlukan untuk mengoptimalkan prestasi belajar anak usia sekolah.